Efficacy and Safety of Allisartan Isoproxil/Amlodipine in Patients With Essential Hypertension Uncontrolled by Amlodipine: A Phase III, Multicenter, Double‐Blind, Parallel‐Group, Randomized Controlled Trial - Hongjie Chi; Xin Zhang; Shumei Ma; Gang Pan; Xiaojuan Lian; Yan Chen; Haotian Pei; Zichen Liu; Xiangmin Lin (The Journal of Clinical Hypertension)
Abstract This study aimed to assess the efficacy and safety of a combination therapy of Allisartan Isoproxil 240 mg and Amlodipine 5 mg (ALI/AML) compared to AML 5 mg monotherapy in patients with mild‐to‐moderate essential hypertension. In this phase III, multicenter, double‐blind, parallel‐group, randomized controlled trial, patients aged 18–70 years with mean sitting systolic blood pressure (msSBP) between 140 and <180 mmHg and mean sitting diastolic blood pressure (msDBP) between 90 and <110 mmHg, following a 4‐week treatment with AML 5 mg, were randomized 1:1 to receive either ALI/AML or AML once daily for 12 weeks. This 12‐week double‐blind period was followed by an open‐label extension of ALI/AML treatment through week 52. A total of 300 patients were enrolled, with 149 and 151 patients randomly assigned to ALI/AML and AML groups, respectively. Of these, 257 patients completed the study. Baseline demographics and characteristics were comparable between groups. After 12 weeks, the reduction in msSBP (the primary endpoint) was significantly greater in the ALI/AML group compared to the AML group (–15.7 vs. –10.2 mmHg, p = 0.0019). Similarly, reductions in msDBP (–5.7 vs. –2.4 mmHg, p < 0.001) and 24‐h mean ambulatory SBP and DBP (–10.4 and –7.7 mmHg vs. –5.6 and –3.8 mmHg) were more pronounced in the ALI/AML group. Additionally, a higher proportion of patients achieved both a BP response and target office BP in the ALI/AML group compared to the AML group (51.4% vs. 37.4%, 42.5% vs. 30.6%, both p < 0.05). The ALI/AML combination was generally well tolerated, and the antihypertensive effect was maintained for up to 52 weeks. In patients with essential hypertension inadequately controlled by AML, the ALI/AML combination provided superior reductions in msSBP and was significantly more effective than AML monotherapy. This once‐daily single‐pill combination demonstrated promising efficacy and tolerability. Trial Registration: ClinicalTrials.gov identifier: NCT06465264